The Implementation of Continuing Professional Development of Economics Teachers at State Senior High Schools in Semarang: Investigating the Constraints and Challenges - Budiyono, Budiyono (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to analyze and investigate the extent in which the implementation of Continuing Professional Development of Economics Teachers at State Senior High Schools in Semarang; barriers in implementing this program; and challenges in the futures when applying this program. This study was a descriptive qualitative research. Data were collected by using questionnaires and interviews. Sample was 27 economics teachers in Semarang. Findings show that personal development by individual teacher and group of teachers in the teacher’s association are more likely to be performed than personal development at a peer group. The major problem in this continuous development is the strict teaching hour. Moreover, the key challenges in the improvement of teaching profession are the way to optimize the role of teachers’ association and the availability of information technology in aiming sustainable professional development.